O corpo contemporâneo: modelação e visibilidades - Silva, Rosa Maria Frugoli da (2007)
This research approaches thematic of the body in the society the contemporary, gift in a gymnastics academy. Such proposal gains importance because the body, today, is retocável and modifiable for the individual in the spaces of modelações and physicist-aesthetic cares, over all in the medium and great urban centers of Brazil. It is observed, for the medias of mass, that the people are constantly being invited to retouch, to take care of, to treat and shape it some detail in its body. When leaving of the idea of that the people whom they frequent this space are stimulated sociocultural to adopt one better quality of life, objective to understand as if gives to the constitution of the body in the society contemporary, having as reference the stories of the citizens that practise physical activity. In specific way, I search to apprehend the sociocultural influences that if reveal in the daily relations produced in this environment identifying the nexus enter the transformations of modernity, its joints, specifications, contradictions. To give account of the defined objectives, I remained of October of 2003 the August of 2004 in the academy; I observed the produced relations there and I interviewed people who frequent that space. The procedures of field work had based on the suggestions of Machado Pais (2003) in the incursion of the daily one, while relations of permanent surprises, and in Clifford Geertz (1989), as for the techniques of interpretation of the symbolic productions. In the systematization of the data, I conclude that the corporal modulation is for beyond the health and, in the passage of the social visibility and of the new identities, the modulated body is one of the main instruments that make possible the production, participation, belonging and access to the goods and values in the contemporaneidade